Eccentric-overload training in team-sport functional performance: constant bilateral vertical versus variable unilateral multidirectional movements - Gonzalo-Skok, O.; Tous-Fajardo, J.; Valero-Campo, C.; Berzosa, C.; Bataller, A. V.; Arjol-Serrano, J. L.; Moras, G.; Mendez-Villanueva, A. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To analyze the effects of 2 different eccentric-overload training (EOT) programs, using a rotational conical pulley, on functional performance in team-sport players. A traditional movement paradigm (ie, squat) including several sets of 1 bilateral and vertical movement was compared with a novel paradigm including a different exercise in each set of unilateral and multi-directional movements.